Analysis of cell identity, morphology, apoptosis and mitotic activity in a primary neural cell culture system in Drosophila. - Moraru, M.M.; Egger, B.; Bao, D.B.; Sprecher, S.G. (Neural Development, 2012)
In Drosophila, most neurogenetic research is carried out in vivo. Mammalian research demonstrates that primary cell culture techniques provide a powerful model to address cell autonomous and non-autonomous processes outside their endogenous environment. We developed a cell culture system in Drosophila using wildtype and genetically manipulated primary neural tissue for long-term observations. We assessed the molecular identity of distinct neural cell types by immunolabeling and genetically expressed fluorescent cell markers. We monitored mitotic activity of cell cultures derived from wildtype and tumorous larval brains. Our system provides a powerful approach to unveil developmental processes in the nervous system and to complement studies in vivo.